Factors That Determine Completion Rates of Biomedical Students in a PhD Programme - Benjamin Benzon; Katarina Vukojevic; Natalija Filipovic; Snježana Tomić; Merica Glavina Durdov (MDPI AG, 2020)
Purpose: The purpose of this retrospective study is to identify potential predictors of academic success or failure in Doctor of Philosophy (PhD) programmes in the field of biomedicine. Based on these, the policies and structure of academic programmes granting PhD degrees in biomedicine might be improved. Literature review (State of the art): At the present moment, most European and all of the EU doctoral education systems in biomedicine are regulated by the Salzburg principles of the Bologna process. Almost all the programmes formally comply with regulations, but the degree to which rules are applied varies greatly. The European Research Council (ERC) and various stakeholders' associations, such as the Organisation for PhD Education in Biomedicine and Health Sciences in the European System (ORPHEUS), have recognised this and in their policies, they recommend regular evaluation of PhD programme structures. One such evaluation that was conducted at our institution motivated us to search for quantifiable factors that can help the process of PhD programme structural reform. Since the literature is scarce on this matter, we decided to conduct analysis of our own data and thus study the relationships between recommended EU policies and real-world data. Methods: Biology of Neoplasms is a PhD programme founded under Bologna process rules. It enrols students with Doctor of Medicine (MD), Doctor of Dental Medicine (DMD) or similar degrees in the biomedical field. A large portion of enrolled PhD students work full time in medical practices. A retrospective analysis was conducted on students who enrolled between 2006 and 2017. In order to quantify academic success, outcome measures of graduation (completion) rate, time to graduation, average impact factor of published papers comprising a PhD thesis and the ratio of the latter two were formed. Age, sex, employment institution, mentor experience and tuition subsidy were considered as potential predictors. Results: A total of 124 students were enrolled in the study-38% male. Out of the total, 21 (16.94%) students discontinued the study programme and 22 students graduated (17.7%). The average impact factor (IF) of published papers was 2.66 ± 1.51. Mentor experience (Odds ratio (OR) = 6.7) and student employment in academia (OR = 11.7) were significant predictors of successful graduation. Stricter criteria for graduation had no effect on graduation in newly enrolled students. Likewise, sex, tuition subsidy and age did not affect graduation rates. Surprisingly, time to graduation was not affected by any of the considered predictors. On the other hand, students that were mentored by experienced mentors and employed in academia outperformed their peers in terms of impact factors of publications related to their thesis. Conclusion: Characteristics such as gender, age at enrolment and even tuition paid by the institution do not have a significant impact on completion rate. Experienced mentors and employment in academic institutions seem to be the factors that predict a successful completion of a PhD programme. Furthermore, our results give a quantifiable support to the ORPHEUS and ERC recommendations and policies. These conclusions can be easily applied to any PhD programme formed under the tenets of the Bologna process.